Does grading undermine feedback? The influence of grades on the effectiveness of corrective feedback on L2 writing. Issue 2 (3rd April 2017) - Dlaska, Andrea; Krekeler, Christian
Abstract : It has been questioned whether students notice, act upon and, ultimately, learn from feedback if feedback about a task is received in conjunction with grades. If grades undermine feedback, it could be argued that it is a waste of teachers' time to add comments to students' written work if the students also receive grades. With reference to SLA (interactionist perspectives) and motivational psychology (achievement goal theory), we viewed the combination of grades and corrective feedback on L2 writing as a 'multiple goal message' and investigated its effect on performance. Three groups of adult learners of German took part in the experiment ( N = 226). Participants produced three texts. Text 1 was written as a draft, text 2 was a revision of the draft and text 3 was an entirely new text on a different topic. The first group received corrective feedback (CF) on all texts (CF-only group), while the second group received grades in addition to the feedback (CF-and-grades group). The third group did not receive CF, but their texts were graded (grades-only group; control group). CF was directed at morphology and syntax only. The study found no significant effects of grading on performance. The results are discussed in the context of SLA and motivational theory. We conclude that the decision to provide CF should not be based on whether a piece of writing is graded or not. For the learners in our study, the effectiveness of feedback depended on other factors.